2013
DOI: 10.1002/cne.23203
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and neurochemical comparisons between pulvinar and V1 projections to V2

Abstract: The flow of visual information is clear at the earliest stages: the retina provides the driving (main signature) activity for the lateral geniculate nucleus (LGN), which, in turn, drives the primary visual cortex (V1). These driving pathways can be distinguished anatomically from other modulatory pathways that innervate LGN and V1. The path of visual information after V1, however, is less clear. There are two primary feedforward projections to the secondary visual cortex (V2), one from the lateral/inferior pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 96 publications
(164 reference statements)
5
42
0
Order By: Relevance
“…In Western blot analysis, it appears as an individual band of ~5 kDa. The staining pattern was identical to the data published for macaques in previous studies that used the same monoclonal VGlut2 antibody (Marion et al 2013; Garcia-Marin et al 2013; Balaram et al 2013). …”
Section: Methodssupporting
confidence: 82%
“…In Western blot analysis, it appears as an individual band of ~5 kDa. The staining pattern was identical to the data published for macaques in previous studies that used the same monoclonal VGlut2 antibody (Marion et al 2013; Garcia-Marin et al 2013; Balaram et al 2013). …”
Section: Methodssupporting
confidence: 82%
“…1) and this corresponds to the known difference in size between the thalamo-cortical and intracortical terminals (Nahnami and Erisir, 2005). It has also been shown recently that the pulvinar terminals in V2 are smaller than those from the LGN to layer 4C of V1 (Marion et al, 2011). In the region of the V1/V2 border, we found that the VGluT2-ir puncta were of different sizes.…”
Section: Discussionmentioning
confidence: 86%
“…Layers 1, 2 and 3 stained strongly for VGLUT1 and weakly for VGLUT2, appearing almost continuous through the extent of V2. Layer 4 contained strong VGLUT2 reactivity, which resembled patterns of pulvinar terminations in V2 (Levitt et al, 1995; Marion et al, 2012, Ogren and Hendrickson, 1977) but relatively weak VGLUT1 staining throughout V2. Layer 5 showed slightly weaker VGLUT1 labeling than layer 4, and diffuse labeling of VGLUT2.…”
Section: Resultsmentioning
confidence: 92%
“…Layer 4 of MT, where V1 projections terminate, showed dense distributions of VGLUT2 positive terminals as well. Layer 4 of V2, which is the primary recipient of feedforward projections from the lateral and inferior pulvinar, as well as V1, also showed dense VGLUT2 terminal labeling as well (Marion et al, 2012). Feedback or modulatory projections from V1 primarily arise in layers 5 and 6 and terminate diffusely in the LGN and superior colliculus, as described above, and these projections are dominated by VGLUT1.…”
Section: Discussionmentioning
confidence: 99%